HESS Opinions: Towards a common vision for the future of hydrological observatories - P. Nasta; G. Blöschl; G. Blöschl; H. R. Bogena; S. Zacharias; R. Baatz; G. De Lannoy; K. H. Jensen; S. Manfreda; L. Pfister; L. Pfister; A. M. Tarquis; et al. (Hydrology and Earth System Sciences)
The Unsolved Problems in Hydrology (UPH) initiative has emphasized the need to establish networks of multi-decadal hydrological observatories to gain a deep understanding of the complex hydrologic processes occurring within diverse environmental conditions. The already existing monitoring infrastructures have provided an enormous amount of hydrometeorological data, facilitating detailed insights into the causal mechanisms of hydrological processes, the testing of scientific theories and hypotheses, and the revelation of the physical laws governing catchment behavior. Yet, hydrological monitoring programs have often produced limited outcomes due to the intermittent availability of financial resources and the substantial efforts required to operate observatories and conduct comparative studies to advance previous findings. Recently, some initiatives have emerged that aim to coordinate data acquisition and hypothesis testing to facilitate an efficient cross-site synthesis of findings. To this end, a common vision and practical data management solutions need to be developed. This opinion paper provocatively discusses two potential endmembers of a future hydrological observatory (HO) network based on a given hypothesized community budget: a comprehensive set of moderately instrumented observatories or, alternatively, a small number of highly instrumented supersites.